Future Circular Lepton Collider Vibrational Crosstalk - Purinut Lersnimitthum; Audrey Piccini; Federico Carra; Tirawat Boonyatee; Niphon Wansophark; Nopdanai Ajavakom (Vibration)
CERN, the European Organisation for Nuclear Research is studying the feasibility of the Future Circular Collider, considering both financial and technical aspects. One of the challenges is that the performance of particle accelerators relies on the dynamic stability of structures, affected by multiple sources of vibrations, including crosstalk vibration between two particle accelerators, the Booster and Collider, in the Future Circular Lepton Collider. This research aims to find a methodology for determining transfer functions, specifically crosstalk transfer functions, between the Collider and Booster within an underground tunnel. Also, it aims to determine how significant crosstalk is compared to the vibration from other sources, such as ground vibrations. The transfer functions of the tunnel were independently determined from internal structures using the Finite Element Method, employing 2D plane strain and the standard absorbing boundary to model the underground tunnel. It was found that the overall gain of crosstalk was less than 10% of that of ground-to-magnetic axis of either the Collider or Booster. This method may be used to optimize the tunnel layout from a vibration point of view. It appears that vibrations from crosstalk are far lower compared to vibrations from ground vibrations.